Bacterial Endosymbionts Are Common Among, but not Necessarily Within, Insect Species. Issue 1 (10th January 2019) - Sazama, Eric J; Ouellette, Scot P; Wesner, Jeff S
Abstract: Bacterial endosymbionts, particularly Wolbachia (Rickettsiales: Rickettsiaceae), Rickettsia (Rickettsiales: Rickettsiaceae), and Cardinium (Bacteroidales: Bacteroidaceae), are commonly found in several arthropod groups, including insects. Most estimates of the global infection rate of Wolbachia (52% [95% credible intervals: 44–60]) show that these bacteria infect more than half of all insect species. Other endosymbionts, such as Rickettsia (24% [confidence intervals [CIs] 20–42]) and Cardinium (13% [CIs 13–55]), infect a smaller but still substantial proportion of insect species. In spite of these observations, it is unclear what proportion of individuals within those species are infected. Here, we used published databases to estimate the proportion of individuals that are infected with either Wolbachia, Rickettsia, or Cardinium . We found that the majority (69%) of Wolbachia- infected species have less than half of their individuals infected with Wolbachia, indicating that although the bacterium may be common among species, it is not common within species. The same was true for Rickettsia (81%) and Cardinium (87%). This discrepancy was consistent across orders, in which less than 10% of individuals were typically infected, even though more than 50% of species within orders were infected. For example, according to our model, nearly 50% of beetle (Coleoptera) species are infected with Wolbachia (i.e., contain at least one individual that has tested positive for Wolbachia ), but less than 5% of all individuals are infected. These results add to the growing knowledge base about endosymbionts in insects and should guide future sampling efforts and investigations on the role that these bacteria play in populations.